Quantification of domestic cat hepadnavirus DNA in various body fluid specimens of cats: the potential viral shedding routes - Wardhani, Sabrina Wahyu; Tummaruk, Padet; Piewbang, Chutchai; Techangamsuwan, Somporn (Frontiers in Veterinary Science, 2023)
Domestic cat hepadnavirus (DCH) belongs to the Hepadnaviridae family together with human hepatitis B virus (HBV) that remains to be a major health problem worldwide. The transmission of HBV infectious virion has been one of the essential factors that contribute to high number of HBV infection in humans. It has been long known that various body fluid specimens of human with chronic HBV infection contain HBV DNA and demonstrated to be infectious. In contrast to this knowledge, the detection of (DCH in various body fluid specimens of cats, has not been reported. This study explored the detection of DCH DNA in various body fluid specimens of cats by quantitative polymerase chain reaction (qPCR) and investigated whether the detection of DCH DNA from broader routes was correlated with any genomic diversity by phylogenetic analysis. A total of 1,209 body fluid specimens were included, and DCH DNA was detected not only in 4.70% (25/532) of blood samples; but also in 12.5% (1/8), 1.14% (1/88), 2.54% (10/394), and 1.65% (3/182) of auricular swab (AS), nasal swab (NS), oral swab (OS), and rectal swab (RS) specimens, respectively. Furthermore, the level of DCH DNA detected in the blood was significantly correlated with DCH DNA detection in OS (P = 0.02) and RS (P = 0.04) specimens. Genomic analysis revealed that there was no notable genomic diversity within the complete genome sequences obtained in this study. In conclusion, this study highlighted the presence of DCH DNA in various body fluid specimens of cats, and the potential role of these specimens in DCH horizontal transmission within the cat population warrants further studies.